Biosynthesis of Silver Nanoparticles from Platymonas sp. and Its Antibacterial Activity Against Biofouling Causing Bacterial Strains. Issue 4 (4th July 2019) - Elangovan, M.; Muju, G.; Anantharaman, P.
Abstract: The present study investigates the antibacterial activity of silver nanoparticles (SNPs) synthesized by biological method using Platymonas sp. Microalgae Platymonas sp. was collected from phytoplankton repository, Tuticorin Research Center of ICAR-CMFRI, Tuticorin, Tamil Nadu, India. Aqueous extract of microalgae was used for the synthesis of silver nanoparticles. Algal extract is used as a reducing agent of 1 mM silver nitrate solution for the synthesis of silver nanoparticles. Periodical monitoring of reaction mixture was done by using UV-Vis spectroscopy at 300-750 nm and synthesis of silver nanoparticles was confirmed by spectrophotometer reading at 425-430 nm. Characterization of SNPs was done by scanning electron microscopy (SEM), energy dispersive x-ray spectroscopy (EDS) and fourier transforms-infrared sepctroscopy (FT-IR). Particle size distribution analysis with SEM shows that the synthesized silver nanoparticles are in the size range of 65.51-82.86 nm. Energy dispersive x-ray spectroscopy (EDS) revealed that silver nanoparticles poised 80.68 % of silver with less chloride (15.25 %). FT-IR spectrum shows absorption bands at 3421, 2358, 1631, 1456.26, 1361.74 and 1240/cm indicating the presence of capping agent with nanoparticles. The antibacterial activity of synthesized silver nanoparticles against pathogens such as Bacillus flexus, Vibrio alginolyticus and Streptococcus sp. was tested with positive control. The zone of inhibition was ranged from 1 to 30 mm against all organisms.